2019
DOI: 10.1002/adfm.201903041
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Self‐Propelled Nanomotors for Explosives Detection via Solution‐Based Surface Enhanced Raman Scattering

Abstract: Nanomotors represent a class of artificial machines that span the chasm between molecular motors and bigger micromotors. Their importance lies in the fact that to effectively navigate and perform tasks in a biological environment without alerting the action of the immune system, the maximal size of the object has to be well below 200 nm. Fully nanosized gold/silver core/shell plasmonic nanomotors using the seeded growth wet chemical approach, which allows high scalability of synthesis of the nanomotors compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 69 publications
(87 reference statements)
0
32
0
Order By: Relevance
“…21,50,51 Such changes in the synthesis methodology bring the shift from 2D production of the nanorobots to voluminous, scalable synthesis. 52,53…”
Section: Practical and Theoretical Challenges Of Nanomotors: The Difference From Micromotorsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,50,51 Such changes in the synthesis methodology bring the shift from 2D production of the nanorobots to voluminous, scalable synthesis. 52,53…”
Section: Practical and Theoretical Challenges Of Nanomotors: The Difference From Micromotorsmentioning
confidence: 99%
“…91 In vivo applied porous silica nanomotors fueled by urease were demonstrated very recently, 32 together with plasmonic nanorobots propelled by hydrogen peroxide decomposition at silver surface with capability of in-situ surface enhanced Raman spectroscopy sensing of explosives. 53…”
Section: Nanorobots With Intrinsic Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, synthetic nanoswimmers may perform diverse operations in the biomedical field, including biosensing [ 13 , 14 ], diagnostics [ 15 , 16 ], precision surgery [ 17 ], laser tissue welding [ 18 ], and direct drug delivery [ 19 , 20 ]. In recent years, various strategies have been employed to propel such micro/nanoswimmers, including chemical reaction [ 21 , 22 ], light stimuli [ 23 25 ], and electric [ 26 , 27 ], magnetism [ 28 , 29 ], and acoustic [ 30 , 31 ] actuation. However, most of the nanoswimmers still rely on inorganic materials, such as SiO 2 , mesoporous silicon, and Fe 3 O 4 ; these formulations often fail to be useable in the biosystem for the systemic toxicity or poor biodegradability.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work reported a self-propelled "match-like" one-dimensional SERS probe driven by photodecomposition of AgCl, where the phototaxis behavior of the nanomotors was utilized to enrich the SERS probes for an additional enhancement of SERS signal [31]. Novotný et al and Han et al reported SERS probes driven by the decomposition of H 2 O 2 for the detection of explosives and Rhodamine 6G, respectively [59,60]. These motor-based SERS probes performed collective behavior (phototaxis or micromixing) for SERS sensing applications.…”
Section: Introductionmentioning
confidence: 99%